"Team Japan Support Center" at the London 2012 Olympic Games - A support base outside the athletes village - Beinert, T. (Asian Conference on sport science. Sport science and elite training programme for world class performance. 25-26 October 2013. Hong Kong Sports Institute, Hong Kong, China, 2013)
The presentation will introduce the concept of "Team Japan Support Center" outside of the Athletes Village at Major Multi Sport Events exclusive for members of the competing Japanese Team. The concept of "Team Japan Support Center" was developed through close communication with National Sports Federations to ensure that it will be a very useful "tool" to help athletes and coaches maximize their performance at the competition.